Genetic Analysis of RadB, a Paralogue of the Archaeal Rad51/RecA Homologue, RadA - Haldenby, Sam (2007)
The integrity of all genomes is under constant threat, with DNA double strand breaks being particularly dangerous. Double strand breaks can be repaired by homologous recombination, a process catalysed by recombinase proteins of the RecA family. The archaeal recombinase, RadA, is homologous to eukaryotic and bacterial Rad51/RecA. Euryarchaea encode an additional Rad51/RecA homologue, RadB. RadB shares homology with the core domain of RadA and has been shown to bind both single and double stranded DNA, binds ATP and possesses a very weak ATPase activity. However, RadB does not catalyse strand exchange. RadB has been shown to interact with RadA, a Holliday junction resolvase (Hjc) and a DNA polymerase (PolD), suggesting a role in recombination. In this study, radB was deleted from the halophilic archaeon, Haloferax volcanii. 'delta' radB strains were slow growing, sensitive to mitomycin C and UV irradiation, and deficient for both crossover and non-crossover recombination. Deletion of radA results in similar phenotypic characteristics, and complete abrogation of recombination. Strains deleted for both radA and radB are equally defective as 'delta' radA strains, demonstrating that RadA is epistatic to RadB. A suppressor of 'delta' radB was isolated and identified as a mutation in the polymerisation domain of RadA (RadA-A196V). radA-A196V suppresses the slow growth, crossover and non-crossover recombination defects associated with 'delta' radB, as well as UV and mitomycin C sensitivity phenotypes. On account of the nature of this suppressor, the observed interaction between RadA and RadB, and the epistatic relationship between RadA and RadB, a role for RadB as a recombination mediator protein is proposed. Finally, strains were deleted for hjc. 'delta' hjc strains exhibit no growth, crossover and non-crossover recombination defects and no UV and mitomycin C sensitivity. This suggests that another, as yet unidentified, Holliday junction resolvase is encoded by Haloferax volcanii.